The unintended consequences of environmental tax for green innovation: Evidence from China - Haohan Luo; Ying Wu (Journal of Applied Economics, 2023)
Can all types of tax burdens negatively affect corporate innovation activities? The Chinese Environmental Protection Tax Law provides a chance to investigate the impact of environmental taxes on corporate green innovation. Using a large sample of Chinese listed firms for the 2015-2019 period and the difference-in-difference method, this paper finds that environmental taxes promote corporate green innovation. This result is robust to a battery of sensitivity tests and is more prominent for firms facing intense product market competition, firms with more financial constraints, and firms located in lower marketization regions. Mechanism tests find that firms engage in green innovation to cater to government environmental governance. Additional analyses find that environmental taxes have a significant effect on green innovation efficiency and green utility model innovation but fail to impact green invention innovations. Our study provides new and different evidence of the impact of taxes on corporate innovation and has important policy implications.
Keywords: 330; China; Chinese Environmental Protection Tax Law; Environmental tax; green innovation